ByzRev 08.2026.018: Ioannis Polemis, An Αuthor in Search of His Place in Time: Mercurius the Grammarian and His Texts (Hellenica 115): Alessandria: Edizioni dell’Orso 2025 - Bazzani, Marina (The Byzantine Review, 2026)
Ioannis Polemis, An Αuthor in Search of His Place in Time: Mercurius the Grammarian and His Texts (Hellenica 115). Alessandria: Edizioni dell’Orso 2025. 170 pp. – ISBN 978-88-3613-628-5